2020
DOI: 10.1108/bepam-11-2018-0151
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy sources and technologies in commercial buildings

Abstract: Purpose The purpose of this paper is to explore the perceptions and experiences of building practitioners in the adoption of renewable energy (RE) in commercial buildings in Nigeria. Design/methodology/approach A qualitative methodology was used guided by the principles of the Grounded Theory Method (GTM). Data were collected using in-depth semi-structured interviews with a purposive sample of five industry practitioners. Findings Five distinct factors emerged, namely, being compliant, change in mindset, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…These SC practices include using indigenous building materials locally rather than transporting construction materials to the site from a more extended or "cross-country" Adaptability capacity framework distance which may contain hazardous substances to human health (Li et al, 2012;Mensah, 2017). Unuigbe et al (2020) admit that applying appropriate technology through research to develop materials that would suit the local environment is a factor that works perfectly with the pressure and release model. According to the resilience concept, the improvement of affordable natural ecological cycled materials such as bamboo is a plus.…”
Section: Conceptual Framework For Adaptive Capacitymentioning
confidence: 99%
“…These SC practices include using indigenous building materials locally rather than transporting construction materials to the site from a more extended or "cross-country" Adaptability capacity framework distance which may contain hazardous substances to human health (Li et al, 2012;Mensah, 2017). Unuigbe et al (2020) admit that applying appropriate technology through research to develop materials that would suit the local environment is a factor that works perfectly with the pressure and release model. According to the resilience concept, the improvement of affordable natural ecological cycled materials such as bamboo is a plus.…”
Section: Conceptual Framework For Adaptive Capacitymentioning
confidence: 99%
“…Research into RET and its potential for building adoption in the Nigerian built environment is not new; however, the available literature is primarily limited in focus to the adoption of PV in the residential sector, or RETs more broadly from a national perspective [31,39,50]. From a residential sector perspective, studies have mostly focused on small-scale, decentralised, standalone power generation for rural use [41,51,52].…”
Section: Retsmentioning
confidence: 99%
“…The study by Unuigbe et al (2020) is the only empirical study identified that sought to investigate REs within the commercial sector. Although it did not generate a theory, it identified cultural-related factors as significant for informing the adoption of RE beyond economic and technical factors often identified in the literature.…”
Section: Retsmentioning
confidence: 99%
“…As well as a growth in office developments due to expanding global markets (Usman et al, 2019). For instance, Unuigbe et al, (2020) note that this is due in part to how they are designed and used, with multiple generators operating as both the main and backup supply over long periods. Generators account for over 90% of the energy supply in organisations (Anyanele et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some research articles were already published in journals, such as Unuigbe et al (2020), Usman, et al (2019), andAdejoro (2017), which are closely related to the authors' paper. The author(s) did not, however, review and provide the key findings of those articles in the paper.…”
mentioning
confidence: 99%